Bottlenecks and inbreeding depression in autotetraploids. (11th September 2018) - Layman, Nathan C.; Busch, Jeremiah W.
Abstract: Inbreeding depression is dependent on the ploidy of populations and can inhibit the evolution of selfing. While polyploids should generally harbor less inbreeding depression than diploids at equilibrium, it has been unclear whether this pattern holds in non‐equilibrium conditions following bottlenecks. We use stochastic individual‐based simulations to determine the effects of population bottlenecks on inbreeding depression in diploids and autotetraploids, in addition to cases where neo‐autotetraploids form from the union of unreduced gametes. With a ploidy‐independent dominance function based on enzyme kinetics, inbreeding depression is generally lower in autotetraploids for fully and partially recessive mutations. Due to the sampling of more chromosomes during reproduction, bottlenecks generally reduce inbreeding depression to a lesser extent in autotetraploids. All else being equal, population bottlenecks may have ploidy‐dependent effects for another reason–in some cases matings between close relatives temporarily increase inbreeding depression in autotetraploids by increasing the frequency of the heterozygous genotype harboring the most harmful mutations. When neo‐autotetraploids are formed by few individuals, inbreeding depression is dramatically reduced, given extensive masking of harmful mutations following whole genome duplication. This effect persists as nascent tetraploids reach mutation‐selection‐drift balance, providing a transient period of permissive conditions favoring the evolution of selfing.